2017
DOI: 10.1016/j.ensci.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functions in newly diagnosed patients with HIV infection in a tertiary health facility: Assessment using community screening interview for dementia

Abstract: IntroductionNeurocognitive dysfunction is a detrimental complication of HIV infection. In this study we attempt to characterize the pattern of cognitive dysfunction in a sample of Nigerian patients with newly diagnosed HIV infection.MethodsWe conducted a prospective study in which 50 patients with newly diagnosed HIV infection were studied along with 50 normal control subjects. The participants were evaluated with the medical history, general, physical and neurological examination. Laboratory evaluation and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…Average age of the study was 34.8 ± 6.86 years. This was relevant to various studies that report almost the same result, Suyanto et al found the age of HIV/AIDS patients between 30 -39 years (35.92%), Jumare et al found the average age of HIV / AIDS patients was 35 ± 9 years in and sumonu et al found the average age of HIV/AIDS patients was 36.44 ± 8.22 years (13,15,16). Vol.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Average age of the study was 34.8 ± 6.86 years. This was relevant to various studies that report almost the same result, Suyanto et al found the age of HIV/AIDS patients between 30 -39 years (35.92%), Jumare et al found the average age of HIV / AIDS patients was 35 ± 9 years in and sumonu et al found the average age of HIV/AIDS patients was 36.44 ± 8.22 years (13,15,16). Vol.…”
supporting
confidence: 54%
“…In this study, the age of the study subjects was younger compared to studies which showed that HIV/AIDS was associated with neurocognitive disorders that gained an average of older age (>45 years). (16,17) Patients with HIV/AIDS infection perform poorly in the domains of language, memory, orientation, attention/calculation and practical relative to control (p<0.05). (13) The study has excluded subjects who were previously diagnosed with neurocognitive disorders before being diagnosed with HIV/AIDS.…”
Section: Research Characteristicsmentioning
confidence: 99%
“…48 Several measures, ranging from generic to disease-specific measures, are used to assess neurocognitive disorder among PLWHIV. These include the popular mini-mental state exam 48 , the HDS 49 , community screening interview for dementia 50 , IHDS 29 , and several combinations of neuropsychological tests such as Hopkins verbal learning test revised, Wechsler adult intelligence scale III symbol search, grooved pegboard, colour trails 2, Wechsler memory scale III spatial span and controlled oral word association test 11 . In this review, cognitive measures included IHDS, HDS, community screening interview for dementia, Montreal Cognitive Assessment Scale and multidomain neuropsychological tests.…”
Section: Discussionmentioning
confidence: 99%
“…Las infecciones oportunistas aumentan la discapacidad, la morbilidad y la mortalidad (42,66,(73)(74)(75)(76). Las infecciones oportunistas se han asociado con trastornos neurocognitivos, con el síndrome inflamatorio de reconstitución inmunitaria, y con limitaciones auditivas, orales y visuales (52,73,(77)(78)(79)(80). Dada la ausencia de datos sobre la discapacidad y la mortalidad causadas por las infecciones oportunistas en Colombia, estas consecuencias no se analizaron en este estudio, por lo que se sugiere incluirlas en posteriores análisis.…”
Section: Discussionunclassified